Organisationa heritage: exploring effects on employee outcomes and perceptions of organisational attractiveness - Pidcock, Leslie G. (Cranfield University, 2017)
This research study is one of the first to explore how Organisational Heritage may affect employees and potential employees. It examines employee outcomes that may be related to heritage and provides insight into the effect heritage can have on potential employees’ perception of organisational attractiveness. The first part of the study focused on heritage characteristics and employees of a Corporate Heritage Brand (CHB). In-depth interviews were conducted with employees of a Canadian CHB to determine if heritage was a significant organisational identity characteristic, to establish which employee outcomes it was likely to influence and to explore the effects it had on the outcomes being identified. Results suggested that heritage characteristics are a distinct part of the organisational identity (the organisational heritage identity) which may positively affect organisational identification, organisational affective commitment, employee engagement, organisational pride and intent to stay. Heritage also appeared to diminish the negative impact of transformational organisational change on employee outcomes. A model is presented that summarizes the findings. The second study used the repertory grid technique to determine the characteristics that a sample of potential employees used to differentiate between employer organisations which included CHB and non-CHB companies. Honey’s content analysis was used to ascertain which of these characteristics positively affect perceptions of organisational attractiveness. The study looked specifically at heritage as an organisational characteristic. The results identified nine characteristics, including heritage, which potential employees use to differentiate amongst employer organisations. Another set of nine characteristics were found to be strongly aligned with organisational attractiveness. Four characteristics were common to both groups, and importantly heritage was a part of these. A matrix is presented that categorises organisational characteristics on two dimensions: potential for differentiation and alignment with organisational attractiveness. Four types of characteristics were defined in the matrix: Key Organisational Identity (KOICs) – high differentiation, high attractiveness, Hygiene – low differentiation, high attractiveness, Differentiator – high differentiation, low attractiveness and Low Value – low differentiation, low attractiveness. Heritage was categorized as a KOIC. The discussion suggests heritage can be key to increasing perceptions of organisational attractiveness and organisational identification. Employer branding can be proactively used to convey the organisational heritage. In general, employer branding efforts to communicate key organisational identity and hygiene characteristics to potential employees can increase the likelihood of inclusion in the potential employees’ employer consideration set. Overall, this research contributes to our increased understanding of heritage in an organisational setting. Specifically, it is one of the first academic efforts to provide empirical evidence in the nascent field of organisational heritage. The first part identified five employee outcomes likely to be affected positively by heritage. The findings also suggested that heritage may diminish the negative impact of organisational change on such organisational outcomes. The second part examined the importance of heritage in regard to potential employees and found evidence that heritage may be activated to differentiate employer organisations and can increase the perceived attractiveness. The findings allowed classifying several elicited organisational characteristics (including heritage) along their potential for organisational differentiation and organisational attractiveness.
Keywords: Organisational heritage; corporate heritage brand; organisational heritage identity; organisational attactiveness; organisational identification; organisational affective commitment; employee engagement; organisational pride; consideration set; employer brand; repertory grid technique; Honey's content analysis